(untitled) (Journal of history, 2021)
The article deals with the history of modern research of medieval sculptures of Saryarka. The results of field studies conducted under the direction of Zh.K. Kurmankulov are analyzed. At this time, the published general works of L.N. Ermolenko, Zh.K. Kurmankulov. L.N. Ermolenko made a significant contribution to the training of sculptures in Central Kazakhstan.For the first time, he analyzed and systematized the Saryarkin medieval sculptures and proposed their iconographic classification. To date, Zh. K. Kurmankulov and L. N. Ermolenko have studied more than 300 medieval statues, of which 111 were recorded for the first time. The researchers of the institution GPS coordinates of the monuments, made dimensional drawings of the statues, made micalent copies of some of the statues or their details, created schematic plans of the weapons with which the statues are connected, and made photofixation. Consideration of the history of field research of monuments of monumental sculpture of Saryarka in the aspects of the development of the field documentation methodology is important, on the one hand, for the Eastern studies assessment of the accumulated scientific documentation, on the other, for determining the satisfaction of the needs in the present time methods of fixing the latest achievements of the field archaeological research methodology. The analysis of the history of the study of the medieval sculptures of Saryarka on Etamp and the assessment of the degree of their study allowed us to formalize the main problems and tasks of further research of these unique monuments. Кey words: Saryarka, statues, Turks, kipchaks, steles, fences, structures, ball balls, archaeological sites